Pengembangan Perangkat Pembelajaran Generatif Berintegrasi Imtak Pada Materi Ajar Listrik Dinamis Bagi Siswa Kelas X MAN 1 Banjarmasin - Fitriah, Lutfiyanti (Berkala Ilmiah Pendidikan Fisika, 2013)
The development of generative learning materials integrated to faith and piety on dynamic electricity subject for the students of class X MAN 1 Banjarmasin. The instructional materials in class X of MAN 1 Banjarmasin so far only designed to make students understanding knowledge of physics or not integrated to faith and piety values. The aim of this research is to describe the effectiveness of the implementation of generative learning materials integrated to faith and piety on dynamic electricity subject for the students of class X MAN 1 Banjarmasin. The specific aims in this research are to describe: (1) feasibility of instructional materials that are developed, (2) lesson plan implementation, (3) result study of product, (4) result study of faith and piety, and (5) students response. This is development research that refers to Dick and Carry model. The research design is one group pretest-posttest design. The validations of instructional materials (lesson plan, hand out, student worksheet, and test) are in feasible category. The class tryout result shows that: (1) lesson plan implementation for each meeting is 100%, (2) results study of product for each meeting are reached classical completeness to 55,56%; 71,88%; and 91,67%, (3)Â  results study of faith and piety for each meeting is reached classical completeness toÂ  33,33%; 96,88%; and 63,89%, and (4) students response to this learning is good. The effectiveness of the implementation of learning is 69,43% so that it could be concluded that generative learning integrated to faith and piety on dynamic electricity subject for the students of class X MAN 1 Banjarmasin is effective to improve student study result. Â